2007
DOI: 10.1007/s11249-007-9267-0
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Dependence of ZnDTP Tribochemical Film Formation: A Combinatorial Approach

Abstract: Combinatorial testing has been performed on zinc dialkyldithiophosphate (ZnDTP)-containing lubricants, to investigate the effects of contact pressure on the formation of tribochemical films. Contact pressures ranging from 25 to 500 MPa were applied in ball-on-disc tribotests with oscillating load. Both the ball and the disc were investigated by means of small-area and imaging X-ray photoelectron spectroscopy (XPS). The thickness and the composition of the reaction layer were estimated from the XPS data. The th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
60
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 56 publications
6
60
1
Order By: Relevance
“…The presence of shorter chain lengths inside the tribotracks compared to the non-contact regions was also previously observed [5,8]. In our previous study [13] it was shown that zinc metaphosphate is depolymerized against steel under sliding conditions.…”
Section: Tribochemical Reaction Of Depolymerizationsupporting
confidence: 77%
See 4 more Smart Citations
“…The presence of shorter chain lengths inside the tribotracks compared to the non-contact regions was also previously observed [5,8]. In our previous study [13] it was shown that zinc metaphosphate is depolymerized against steel under sliding conditions.…”
Section: Tribochemical Reaction Of Depolymerizationsupporting
confidence: 77%
“…This may explain why, despite more than 70 years of extensive research, the mechanisms of film formation and wear protection of the most common and successful class of anti-wear addives, Zinc dialkyldithiophosphates (ZnDTPs), are still incompletely understood [2,3]. ZnDTP is known to react at the steel interface, forming a tribofilm with thickness, chemical and physical properties that are dependent on conditions such as applied load, temperature, and additive concentration [4][5][6][7]. The composition of the tribofilm is heterogeneous, characterized by a pad-like structure and mainly constituted of amorphous zinc and iron polyphosphates [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations